An Exploration of Risks Involved in Managing Supplier Portfolio in Multinational Companies Operating in Indonesia - Nova Sepadyati (Institute of Research and Community Outreach - Petra Christian University, 2019)
Outsourcing applications have widely used and regarded as a primary strategic management tool by firms. However, particularly in the Fast Moving Consumer Goods (FMCG) industry, most companies have at least once declined from a renewing contract with the same service provider. There have not been any studies regarding risk management in a buyer-supplier relationship in multinational companies (MNCs) from developed countries operating in an emerging country, particularly in Indonesia. The purpose of this qualitative study is to find out how MNCs in the FMCG sector in Indonesia choose their suppliers, risk perceived, and how they manage their relationship with different suppliers to ensure their performance. Buyer's previous experience, time/cost pressure, and company's culture proved to influence companies in selecting suppliers. Key risks perceived by companies mainly regarding unperformed suppliers, supplier's opportunistic behaviour, and unstable economic/political condition. To ensure a supplier's performance, companies need to set different relationship positioning for each activity outsourced through a proper type of contract and aligned performance measurement. Moreover, a formal supplier rating has not found in all companies, let alone supplier development initiatives.